Designing for Fit: An Iterative Ergonomic Car Trash Bin Prototype via Design Thinking and House of Quality - Pratama Jaya; Edna Maryani; Steela Apfiasari; Cipto Purwanto (Manunggal Halim Jaya, 2026)
Vehicle interior cleanliness affects travel comfort, particularly when a car is used by families or multiple passengers. This study developed and tested an ergonomic car trash-bin prototype using Design Thinking and Quality Function Deployment through the House of Quality (HoQ). The study used archived product-development evidence, including aggregate questionnaire charts, an empathy map, existing-product observations, brainstorming records, HoQ, hand sketches, fabrication videos, static-fit photographs, and prototype-testing documentation. Because respondent-level questionnaire data were not retained, the analysis was descriptive and did not use inferential statistics. Three user needs were prioritised: easy reach, no interference with passenger movement, and prevention of waste scattering. The documented initial under-seat concept measured 440 x 450 x 200 mm and did not fit the selected vehicle space. After cardboard trials at the highest and lowest seat positions, the revised under-seat design measured 280 x 250 x 100 mm and achieved documented static fit. An initial door-trim trial was blocked by the cavity geometry; a custom door-pocket configuration of 160 x 65 x 130 mm was subsequently documented in static placement. The 2 mm black-acrylic prototype was assessed only for basic fit and intended use. The findings support vehicle-specific product development and identify the need for dynamic driving, usability, and cost-validation tests. For automotive-accessory designers and small manufacturers, this record offers a practical, replicable reference for translating cabin-cleanliness complaints into a vehicle-specific prototype before committing to tooling and mass production.